A meta-analysis of the effects of angiotensin converting enzyme inhibitors and angiotensin II receptor blockers on insulin sensitivity in hypertensive patients without diabetes. Issue 3 (March 2015) - Yang, Yue; Wei, Ri-bao; Wang, Zi-cheng; Wang, Na; Gao, Yu-wei; Li, Min-xia; Qiu, Qiang
Highlights We collect the data of insulin sensitivity with hypertensive patients. A total of 203 cases of patients involved in 4 clinical studies were included. ACEI is more effective than ARB on improve insulin sensitivity. ACEI and ARB do not show significant differences with FPG, FPI and BP.